Control químico de malezas en arroz (Oryza sativa L) bajo riego en la zona de Babahoyo - Mora Carbo, Alvaro Antonio (2018)
VIII. SUMMARY The present experimental work was carried out on the grounds of the experimental farm "Palmar", located at Km 10.5 of the Babahoyo-Montalvo road. Objective: 1) Determine the degree of effectiveness of the herbicides used in the control of weeds in rice cultivation; 2) Identify the most effective and economic treatment in the control of weeds and 3) Evaluate the phytotoxic effect of the treatments on the crop. The types of herbicides studied were: herbicides graminicides and broad-leaved herbicides and cyperaceae. Conclusions: : it was determined that the most predominant weeds were Fimbristylis miliacea with 161,02 and Ischaemum rugosum with 76,72 plants/m2 with a high equivalent significance; The application of Fenoxaprop-p-ethyl caused the highest phytotoxicity to the culture at 7 and 14 days with values of 4, equivalent to moderate damage, the remaining treatments only caused phytotoxicity at 7 days with values of 1, equivalent to little damage; The most effective and economical treatment was obtained with the mixtures of Metsulfuron methyl + Bispiribac sodium with a control of 80,24; No treatment was effective to control Ischaemum rugosum; The highest number of tillers was obtained with the mixture of Pyrazosulfuron ethyl + pendimentalin with 452,00 tillers / m2; The highest plant height at 30 days was reported by the mixture of Bispiribac sodium + Pyrazosulfuron ethyl with 64,40 cm, while at 60 and 90 days the application of Quinclorac obtained the highest height with 113,23 and 138,97 cm respectively; The application of Quinclorac obtained the highest weight value of 100 grains with 27,35 g; The highest yield of the crop was presented with the mixture of Metsulfuron methyl + Bispiribac sodium with 6700,00 kg / ha; In economic analysis, satisfactory benefits were obtained, highlighting the mixture of Metsulfuron methyl + Bispiribac sodium with a net benefit of $ 1127,78.